Assessment of soil loss tolerance through statistical and fuzzy techniques in submontane Punjab - HADDA, M. S.; CHANDEL, SUMITA; SINGH, SANDEEP (Journal of Soil and Water Conservation, 2017)
Land degradation in the form of water erosion is major challenge in the submontane Punjab. This poses great threat to sustainability and productivity of agriculture in the area. The soil loss tolerance (T–value) serves as an ultimate criterion for determining if erosion control measures are necessary to preserve and maintain long term soil productivity. Keeping this in view, a study was conducted with the objective to assess the soil loss tolerance in submontane Punjab using five factors viz., infiltration rate, bulk density, erodibility, organic carbon and soil pH. The established relationship between five factors and corresponding indicators was employed to transform each indicator into unit less scale in the form of 0 to 1. Thus, employing aggregated score, the soils were grouped into 3 groups viz., I, II and III. The results indicated that Majari soils were less tolerant to soil loss with low aggregate score and belong to soil group I. However, the soils of Ballowal-Saunkhari were more tolerant to soil loss in the surface layers over the soils of other locations viz., Binewal, Dallewal, Bhadiar and Kokowal. The sub-surface and sub-sub-surface soils of the locations Kokowal, Binewal, Dallewal and Bhadiar showed higher Tvalue. It, thus, suggested maintaining soil productivity at sustainable levels at each location by reducing the erosion risk.